2011
DOI: 10.1590/s0103-50532011000500012
|View full text |Cite
|
Sign up to set email alerts
|

Square wave voltammetric determination of Dexamethasone on a multiwalled carbon nanotube modified pencil electrode

Abstract: O comportamento eletroquímico de dexametasona, um hormônio esteroidal, foi estudado em um eletrodo de grafite modificado por nanotubos de carbono de camadas múltiplas, por voltametria de onda quadrada e espectroscopia de impedância eletroquímica. Dexametasona mostrou um pico de oxidação com potencial em torno de + 0,80 V na superfície do eletrodo modificado. Sob condições ótimas, a corrente de pico de oxidação depende da concentração da dexametasona e foi linear no intervalo de 0,15-100 μmol L -1 de dexametaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Moreover, as can be seen in the Experimental section, these samples were collected in areas with a large presence of sediments, detritus rich in organic matter, where its mineralization is associated to environmental conditions, such as redox potential, dissolved oxygen, pH and temperature, 1 indicating the likely presence of humic acids. Studies with natural waters showed that these substances can interact with other dissolved compounds in the environment, 14,29 in this case DMZ molecules, which can reduce their concentration in the electrochemical cell. Recently, Botero et al 7 showed that some drugs can interact with ionized oxygenated groups of aquatic humic substances, through hydrogen bonds, which can strongly influence the transport and reactivity of these contaminants in aquatic systems.…”
Section: Application Of the Methods In Raw Natural Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as can be seen in the Experimental section, these samples were collected in areas with a large presence of sediments, detritus rich in organic matter, where its mineralization is associated to environmental conditions, such as redox potential, dissolved oxygen, pH and temperature, 1 indicating the likely presence of humic acids. Studies with natural waters showed that these substances can interact with other dissolved compounds in the environment, 14,29 in this case DMZ molecules, which can reduce their concentration in the electrochemical cell. Recently, Botero et al 7 showed that some drugs can interact with ionized oxygenated groups of aquatic humic substances, through hydrogen bonds, which can strongly influence the transport and reactivity of these contaminants in aquatic systems.…”
Section: Application Of the Methods In Raw Natural Watersmentioning
confidence: 99%
“…[13][14][15] Electroanalytical methods can be interesting alternatives for this purpose, due to their sensitivity, selectivity, and relatively short time of analysis in comparison with traditional analytical procedures. [15][16][17][18] Square-wave adsorptive voltammetry (SW-AdsV) is a wellestablished and fast electroanalytical technique and has been applied in the analysis of DMZ in different matrices, such as pharmaceutical preparations and biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Voltammetric sensors based on carbon electrodes present a wide potential window and low capacitive current. Owing to these characteristics, they have been successfully used in the quantification of different pharmaceutical products 1317. Moreover, carbon electrodes can be readily coupled with flow system analysis (FIA) or used in association with batch injection analysis (BIA) during amperometric analysis 18–21.…”
Section: Introductionmentioning
confidence: 99%
“…In coupling an electrochemical method with LPME for trace analysis, type and shape of the working electrode affect the voltammetric results [30][31][32]. For this reason, different types and shapes of working electrodes have been tested in voltammetric methods, among which the multiwall carbon nanotubes-modified graphite electrode has proved to be a suitable one [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, different types and shapes of working electrodes have been tested in voltammetric methods, among which the multiwall carbon nanotubes-modified graphite electrode has proved to be a suitable one [32,33]. In this work, multiwall carbon nanotubes (MWCNTs) were used for modifying a pencil graphite electrode to develop a sensitive and useful tool for the determination of buprenorphine.…”
Section: Introductionmentioning
confidence: 99%